2011
DOI: 10.1194/jlr.m010215
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine supplementation reverses methionine restriction effects on rat adiposity: significance of stearoyl-coenzyme A desaturase

Abstract: Stearoyl-CoA desaturase-1 (SCD1) is a key enzyme in fatty acid and energy metabolism, but little is known about its nutritional regulation. Dietary methionine restriction in rats decreases hepatic Scd1 mRNA and protein, increases energy expenditure, and decreases fat-pad mass/body-weight% (FM/BW%). In humans, plasma concentrations of the methionine product, cysteine, are associated with obesity. To determine which consequences of methionine-restriction are mediated by decreased cysteine availability, we monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 54 publications
(112 reference statements)
16
138
1
1
Order By: Relevance
“…In agreement with reports showing a positive association between cysteine levels and body mass index (BMI) in humans [8], the supplementation of the MR diet with cysteine was shown to reverse the MR-mediated effects on adiposity and serum parameters associated with adiposity suggesting that lowered cysteine levels contribute to MR’s effects on body composition [9]. Although cysteine supplementation was demonstrated to reverse MR’s effects on the transcription of the stearoyl-CoA desaturase 1 (Scd1) gene [9] which has been linked with obesity and insulin resistance [10], there is little insight regarding the other consequences of MR and, subsequently, lowered cysteine levels that dictate the lean phenotype and insulin sensitivity in F344 rats. …”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In agreement with reports showing a positive association between cysteine levels and body mass index (BMI) in humans [8], the supplementation of the MR diet with cysteine was shown to reverse the MR-mediated effects on adiposity and serum parameters associated with adiposity suggesting that lowered cysteine levels contribute to MR’s effects on body composition [9]. Although cysteine supplementation was demonstrated to reverse MR’s effects on the transcription of the stearoyl-CoA desaturase 1 (Scd1) gene [9] which has been linked with obesity and insulin resistance [10], there is little insight regarding the other consequences of MR and, subsequently, lowered cysteine levels that dictate the lean phenotype and insulin sensitivity in F344 rats. …”
Section: Introductionsupporting
confidence: 73%
“…table S2). Because MRC reverses MR’s effects on adiposity and serum parameters [9], microarray analyses were also conducted in tissues from MRC rats. At the same cutoff values of 1.5-fold and p ≤ 0.05, MRC significantly upregulated 61 genes and downregulated 25 genes in liver, upregulated 4 genes and downregulated 9 genes in inguinal adipose tissue, and upregulated 15 genes and downregulated 8 genes in quadriceps muscle (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 As shown in Figure 3, the expression levels of Scd1 and Pparg in liver and adipose tissue were significantly greater in the SHR progenitor strain than in the SHR-Folr1 transgenic strain, which ectopically expresses Folr1 in these tissues. However, the expression levels of these genes were also greater in liver and fat tissue of the SHR compared with that in the SHR congenic strain, which does not ectopically express Folr1 in these tissues.…”
Section: Folr1 and Metabolic Disturbances In The Shr 339mentioning
confidence: 96%
“…In the SHR compared with the Folr1 congenic and transgenic strains, increased plasma concentrations of cysteine and glycine, and decreased plasma concentrations of methionine and serine, would be consistent with a decreased rate of homocysteine remethylation due to relative deficiency of folate. 22 Recent studies suggest that alterations in cysteine levels may influence risk for obesity through effects on expression of Scd1, 16,17 which may be mediated in part via transcriptional effects of PPARγ. This raises the possibility that the greater cysteine levels in SHR than in the Folr1 congenic and transgenic strains may be contributing to greater risk for obesity and related metabolic disturbances via effects on Scd1.…”
Section: Discussionmentioning
confidence: 99%
“…Ironically, the plasma cysteine level is positively correlated with the body weight and BMI. 38) Elshorbagy et al 37) have reported that supplementation with 0.5% L-cysteine annulled the anti-obesity effect in rats on a methionine-restricted diet. However, they found that adding this level of L-cysteine to the control diet decreased the food intake and adiposity.…”
Section: Discussionmentioning
confidence: 99%